Β‐Cryptoxanthin uptake in THP‐1 macrophages upregulates the CYP27A1 signaling pathway. Issue 3 (1st October 2013) - Fu, Hongfei; Wu, Canjie; Riaz, Hasan; Zhang, Hualin; Han, Li; Bai, Liya; Yang, Feifei; Yang, Liguo
<x xml:space="preserve">Abstract</x> Scope Mitochondrial sterol 27‐hydroxylase (CYP27A1), a mediator of cholesterol homeostasis, is reported to exhibit antiatherogenic properties. Many studies suggested that all‐trans retinoic acid can be used to treat atherosclerosis through retinoic acid receptor (RAR)‐mediated upregulation of CYP27A1 expression. In this study, we hypothesized that β‐cryptoxanthin (β‐cry), as a natural ligand of RAR, might act as antiatherogenic agent by upregulating CYP27A1. Methods and results We found that β‐cry treatment significantly upregulated genes involved in the uptake, transport, and metabolism of retinoids and the signaling pathway of CYP27A1 expression in THP‐1 macrophages as detected by microarray analysis. Meanwhile, intracellular levels of β‐cry were correlated to the concentration and exposure time of the treatment. The expression of genes, involved in signaling pathway of CYP27A1, was dramatically decreased due to repressed activity of RAR. Higher level of 27‐hydroxycholesterol was detected in β‐cry‐treated macrophages by HPLC. Docking simulation showed that β‐cry could interact with cellular retinoic acid binding protein 2. These findings were further confirmed through microarray results. Conclusion Our results provide strong evidence that β‐cry can be actively taken up by THP‐1 macrophages and exhibits antiatherogenic effect on THP‐1 macrophages by inducing CYP27A1 expression via RAR.